Peningkatan Nilai Tambah Komoditas Labu Madu (Butternut Squash) Menjadi Keripik Labu Madu - Muhammad Hasyim Ashari; Firdaus Intania (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
PkM aims to increase the added value of the honey pumpkin commodity (butternut squash) from community agriculture into processed food products in the form of honey pumpkin chips. The stages of implementing this activity are stages (1) socialization of activities to honey pumpkin farming communities and business partners, (2) selection of raw materials, preparation of tools and other infrastructure, (3) processing practices and manufacturing procedures for processing honey pumpkin chips, (4) assistance in the process of licensing home industry products (P-IRT) and halal certification, (5) training on selling price calculations, (6) marketing training and entrepreneurship assistance, and (7) monitoring and evaluation of activities. The results of this service activity provide an alternative solution for the honey pumpkin farming community in marketing their agricultural commodity products in the form of honey pumpkin chips that have been standardized by the presence of procedures and have the legality of P-IRT licensing so that it will be easy to market the processed food products. The conclusion of this service is that the honey pumpkin chips product is an alternative option to increase added value for honey pumpkin farmers to achieve family welfare. With the results of this community service activity, it is hoped that it can increase public consumption of honey pumpkin products in the form of honey pumpkin chips which will have an impact on improving the welfare of honey pumpkin farmers.